2020
DOI: 10.1136/ijgc-2019-000904
|View full text |Cite
|
Sign up to set email alerts
|

Frozen section examination of sentinel lymph nodes can be used as a decisional tool in the surgical management of early cervical cancer

Abstract: IntroductionSentinel lymph node (SLN) detection has been shown to be accurate in detecting lymph node involvement in early-stage cervical cancer. The objective of this study was to evaluate the accuracy of frozen section examination in the assessment of SLN status, with the aim of adequately driving the intra-operative decision.MethodsWe designed a retrospective study including patients from two comprehensive cancer centers between January 2001 and December 2018 with early-stage cervical cancer (IA1-IB2 accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 24 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…The ultrastaging of sentinel lymph node detects low-volume metastasis. Frozen section examination of the sentinel lymph node is an acceptable technique; however, it should only be performed by an expert pathologist [34]. The risk of a false-negative frozen section is not negligible, especially in low-volume disease [35].…”
Section: Principles and Results Of Dargent Radical Trachelectomymentioning
confidence: 99%
“…The ultrastaging of sentinel lymph node detects low-volume metastasis. Frozen section examination of the sentinel lymph node is an acceptable technique; however, it should only be performed by an expert pathologist [34]. The risk of a false-negative frozen section is not negligible, especially in low-volume disease [35].…”
Section: Principles and Results Of Dargent Radical Trachelectomymentioning
confidence: 99%
“…As a reminder, FSE is recommended in the guidelines but carries some intrinsic limitations. A retrospective study retained a sensitivity of 81% and an NPV of 97.9% of FSE (with ITCs being excluded from the study) [40]. The SENTIX trial found that FSE failed to detect 54% of positive lymph nodes, especially MIC (90% of cases) [24].…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative SLN status assessment has a variable diagnostic value and frozen sections of SLN are not sufficiently reliable yet, especially for low-volume metastases [ 21 , 41 , 42 , 43 ] even if their prognostic value is still a subject of debate [ 44 , 45 ]. Ultrastaging is required to identify missed micrometastases and macrometastases.…”
Section: Discussionmentioning
confidence: 99%